2017
DOI: 10.1155/2017/6147294
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Pulmonary Arterial Endothelial Cell Transdifferentiation Possibly by Akt and Erk1/2 Pathways

Abstract: This study aimed to investigate the effects and mechanisms of quercetin on pulmonary arterial endothelial cell (PAEC) transdifferentiation into smooth muscle-like cells. TGF-β1-induced PAEC transdifferentiation models were applied to evaluate the pharmacological actions of quercetin. PAEC proliferation was detected with CCK8 method and BurdU immunocytochemistry. Meanwhile, the identification and transdifferentiation of PAECs were determined by FVIII immunofluorescence staining and α-SMA protein expression. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Increasing evidence has demonstrated that the Akt/mTOR signaling pathway is activated and involved in PAH via vasoconstriction and remodeling (47). Furthermore, blocking the Akt/mTOR signaling pathway reverses PAH in animal models (48,49). The present study indicated that SIRT1 upregulated Akt/mTOR in endothelial cells under hypoxic conditions.…”
Section: Discussionsupporting
confidence: 54%
“…Increasing evidence has demonstrated that the Akt/mTOR signaling pathway is activated and involved in PAH via vasoconstriction and remodeling (47). Furthermore, blocking the Akt/mTOR signaling pathway reverses PAH in animal models (48,49). The present study indicated that SIRT1 upregulated Akt/mTOR in endothelial cells under hypoxic conditions.…”
Section: Discussionsupporting
confidence: 54%
“…Our group also demonstrated that quercetin exerted vasodilator effect in isolated pulmonary arteries, induced apoptosis and inhibited cell proliferation in PASMC [106]. The mechanism involved in the antiproliferative effects in both PASMC and endothelial cells seem to involve AKT [106,108,109], FOXO1-mTOR [110], and altered Bax/Bcl-2 ratio [108,111].…”
Section: Flavonoids and Other Polyphenolsmentioning
confidence: 75%
“…Many studies have reported the anti-PH effects of these compounds in vitro and in vivo. Studies demonstrate that quercetin can inhibit pulmonary arterial endothelial cell transdifferentiation into smooth muscle-like cells by regulating Akt and ERK1/2 pathways and enhance the autophagy of PASMCs induced by hypoxia through the FoxO1-SENS3-mTOR pathway [27,28]. Quercetin can also interfere with the IRE1α-XBP1 pathway and TrkA/kt pathway, leading to reduced PASMC migration and cell cycle arrest, which in turn ameliorates hypoxia-induced PH [29,30].…”
Section: Discussionmentioning
confidence: 99%